Treatment practices for geriatric type II odontoid fractures – A survey by the European Association of Neurosurgical Societies Spine Section - Ralph T. Schär; Jefferson R. Wilson; Marcel Ivanov; Giuseppe Barbagallo; Yana Petrova; Carla Reizinho; Maria Luisa Gandia González; Enrico Tessitore; Andrzej Maciejczak; Nikolay Gabrovsky; Bart Depreitre; Ehab Shiban; et al. (Brain and Spine)
Introduction: Controversy exists regarding the optimal management of type II odontoid fractures in the geriatric population. The objective of this study was to determine the current treatment patterns of spine surgeons for geriatric patients (≥70 years) with type II odontoid fractures. Research question: How much do treatment practices for type II odontoid fractures in the geriatric population differ amongst spine surgeons? Methods: The European Association of Neurosurgical Societies (EANS) Spine Section distributed a 39-items web-based survey among spine surgeons between July 2024 and February 2025. Results: A total of 154 responses were collected from 119 neurosurgeons (77.8 %) and 34 orthopedic surgeons (22.2 %). Participants were predominantly from Europe (92.7 %), and 63.2 % have been in practice >10 years. Fracture displacement, comorbidities and age were the most influential factors for decision-making. For non-displaced fractures, 78.8 % of respondents recommended conservative treatment for patients aged 70–80 years, and 83.7 % for those aged 80–90 years. For displaced fractures, 70.9 % preferred surgery for patients aged 70–80 years, whereas this preference decreased to 47.9 % for those aged 80–90 years. Posterior C1-2 fixation was the most common technique for 67.3 % of respondents, and 48.3 % prescribe a collar postoperatively. 51.3 % routinely order CT imaging postoperatively to assess for bony fusion. For conservative treatment, 59.3 % prescribe an external orthosis for 3 months. Discussion and conclusion: Our survey found both variability and consistency in treatment practices of geriatric type II odontoid fractures, reflecting the ongoing debate and lack of consensus in clinical decision-making.